Roman Roads in Tebessa Region - boukef, farida (The Algerian Historical Journal, 2026)
The diversity and richness of the archaeological heritage in the Tebessa region reflects its historical and civilizational importance, and shows the geographical location strategy that the city of Tebessa takes, which made it a human inhabited place from prehistoric times to the present day; It was one of the North African cities that increased in importance and fame at the end of the first century AD with the presence of the Third Augustus Legion in it; who transformed the Numidian paths into a network of real roads; It carried Roman standards, served Rome's military, settlemen, political and economic purposes, and helped urban stability and prosperity; Cities, cultural centers, and rural communities were formed along those roads and at their ends